Computing and network sustainability : proceedings of IRSCNS 2016 - Vishwakarma, H. R., 1960-; Akashe, Shyam (Springer, 2017)
The book is compilation of technical papers presented at International Research Symposium on Computing and Network Sustainability (IRSCNS 2016) held in Goa, India on 1st and 2nd July 2016. The areas covered in the book are sustainable computing and security, sustainable systems and technologies, sustainable methodologies and applications, sustainable networks applications and solutions, user-centered services and systems and mobile data management. The novel and recent technologies presented in the book are going to be helpful for researchers and industries in their advanced works.
Keywords: Computer networks -- Congresses.; Computer networks -- Security measures -- Congresses.; elektronické knihy; electronic books